(100) Plane β-Ga2O3 Flake Based Field Effect Transistor and Its Hydrogen Response. (30th December 2021) - Kim, Man-Kyung; Kim, Yukyung; Bae, Jinho; Kim, Jihyun; Baik, Kwang Hyeon; Jang, Soohwan
Abstract : 2-dimensional (100) plane β phase Ga2 O3 ( β -Ga2 O3 ) flake based field effect transistor (FET) was fabricated, and its electrical characteristics was analyzed. The (100) plane β -Ga2 O3 flake was mechanically exfoliated from the side wall of 2 ̄ 01 plane β -Ga2 O3 bulk substrate. The minimum thickness of 57.3 nm was obtained for the very thin (100) plane β -Ga2 O3 channel layer of the FET using inductively coupled plasma etching with BCl3 /N2 chemistry. The current-voltage characteristics of the FET with various β -Ga2 O3 channel thickness was investigated. The dependence of the channel thickness on the drain current density, threshold voltage, transconductance, and field effect mobility was studied. The hydrogen response of the (100) plane Ga2 O3 flake based FET with catalytic Pt gate surface was measured in the range of 10–500 ppm at 400 °C, and modeled with a dissociative Langmuir isotherm. The device showed a reliable responsivity to the different concentration of hydrogen exposure, and the responsivity of 25.02% was observed for the 500 ppm hydrogen at 400 °C.